Corrigendum to “Surface mineral deposition and mechanical properties of one-step bonding agent with copper-modified niobium nanoparticles – An in vitro study” [Int J Adhesion Adhes 133 (2024) 103764] (International Journal of Adhesion and Adhesives (2024) 133, (S0143749624001465), (10.1016/j.ijadhadh.2024.103764)) - Obeid, Alyssa Teixeira; Mattar de Amoêdo Campos Velo, Marilia [UNESP]; Rita de Lima Nascimento, Tatiana; Sandes de Lucena, Fernanda; Paula de Melo Alves Guedes, Ana; Almeida, Ana Zélia Falcão; Nunes dos Santos, Adriana; Spironelli Ramos, Carlos Alberto; Lia Mondelli, Rafael Francisco; Soares Bombonatti, Juliana Fraga (Elsevier, 2024)
<Note to JM: Errors in article heads, particularly titles, author names, affiliations must not be repeated. In such cases, use the correct title, authors, affiliation(s), etc. If the corrigendum is the result of authorship changes, include the correct author details in the article head.> The authors regret Alyssa Teixeira Obeida∗, Marilia Mattar de Amoêdo Campos Velob, Tatiana Rita de Lima Nascimentoc, Fernanda Sandes de Lucenad, Ana Paula de Melo Alves Guedese, Ana Zélia Falcão Almeidae, Adriana Nunes dos Santosf, Carlos Alberto Spironelli Ramosg, Rafael Francisco Lia Mondellia, Juliana Fraga Soares Bombonattia. The authors would like to apologise for any inconvenience caused.